2020
DOI: 10.1155/2020/4253457
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Facilitates Postconditioning Cardioprotection through Both AMPK-Dependent Nuclear and AMPK-Independent Mitochondrial STAT3 Activation

Abstract: Myocardial ischemic postconditioning- (IPo-) mediated cardioprotection against myocardial ischemia-reperfusion (IR) injury needs the activation of signal transducer and activator of transcription 3 (STAT3), which involves adiponectin (APN). APN confers its biological effects through AMP-activated protein kinase- (AMPK-) dependent and AMPK-independent pathways. However, the role of AMPK in APN-mediated STAT3 activation in IPo cardioprotection is unknown. We hypothesized that APN-mediated STAT3 activation in IPo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…These authors were interested in the involvement of 5' Adenosine Monophosphate-activated protein kinase (AMPK) in IPostC and they found that STAT3 phosphorylation was not affected by the inhibition of AMPK, as well as the protective effects of IPostC were not abrogated, suggesting that IPostC in vitro relies on STAT3 and this is independent of AMPK signaling. In vivo model of MI achieved with LAD occlusion gave similar results with IPostC, increasing the level of S727 but not Y705 phosphorylation of STAT3 [ 250 ]. Moreover, they compared IPostC to pharmacological postconditioning with Adiponectin and they found that while IPostC induced STAT3 activation by S727 phosphorylation, the latter activated/phosphorylated STAT3 in Y705, supporting the difference between ischemic and pharmacological conditioning.…”
Section: Stat3 In Cardiac Conditioningmentioning
confidence: 97%
See 2 more Smart Citations
“…These authors were interested in the involvement of 5' Adenosine Monophosphate-activated protein kinase (AMPK) in IPostC and they found that STAT3 phosphorylation was not affected by the inhibition of AMPK, as well as the protective effects of IPostC were not abrogated, suggesting that IPostC in vitro relies on STAT3 and this is independent of AMPK signaling. In vivo model of MI achieved with LAD occlusion gave similar results with IPostC, increasing the level of S727 but not Y705 phosphorylation of STAT3 [ 250 ]. Moreover, they compared IPostC to pharmacological postconditioning with Adiponectin and they found that while IPostC induced STAT3 activation by S727 phosphorylation, the latter activated/phosphorylated STAT3 in Y705, supporting the difference between ischemic and pharmacological conditioning.…”
Section: Stat3 In Cardiac Conditioningmentioning
confidence: 97%
“…Zhu et al [ 250 ] found that IPostC, in primary rat ventricular cardiomyocytes exposed to H/R, is able to reduce H/R-induced cell damage, with concomitant enhancement of STAT3 phosphorylation S727 but not at Y705. These authors were interested in the involvement of 5' Adenosine Monophosphate-activated protein kinase (AMPK) in IPostC and they found that STAT3 phosphorylation was not affected by the inhibition of AMPK, as well as the protective effects of IPostC were not abrogated, suggesting that IPostC in vitro relies on STAT3 and this is independent of AMPK signaling.…”
Section: Stat3 In Cardiac Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…IPo was established by the group of Vinten-Johansen (Zhao et al, 2003) who first reported 3 cycles of 30 s reperfusion/30 s reocclusion immediately at the onset of reperfusion after 60 min of LAD occlusion. A recent study showed that 3 cycles of 10 s of reocclusion and 10 s of reperfusion at the onset of reperfusion conferred cardioprotection by reducing ROS production through AMPKindependent activation of STAT3 at Ser727 (Zhu et al, 2020). The myocardial protective effect of IPo also relies on regulating energy homeostasis and the expression of myocardial mitochondrial proteins (Cao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin treatment is shown to induce the activation of ceramidase (CDase) and subsequently prevents apoptosis of isolated ventricular cardiomyocytes from obese mice through the degradation of ceramides [ 60 ]. Adiponectin has been shown to involve myocardial ischemic postconditioning (IPo)-mediated cardioprotection against myocardial ischemia–reperfusion (IR) injury in rodents via both AMPK-dependent nuclear and AMPK-independent mitochondrial signal transducer and activator of transcription (STAT)3 activation [ 61 ]. Adipo KO mice exhibited enhanced myocardial apoptosis, infract size, levels of nitric oxide (NO), inducible nitric oxide synthase (iNOS), superoxide, and their cytotoxic reaction products, peroxynitrite, in cardiac tissues [ 62 ].…”
Section: Pleiotropic Role Of Adiponectinmentioning
confidence: 99%